MANAJEMAN PENGELOLAAN BANK WAKAF MIKRO DALAM PEMBERDAYAAN EKONOMI UMAT (STUDI BANK WAKAF MIKRO PONDOK PESANTREN AS’AD KOTA JAMBI) - Khatami Asshidiqqi; Sucipto Sucipto; Bambang Kurniawan (Manajemen Keuangan Syariah, 2023)
This research is entitled Management of Micro Waqf Banks in Empowering the People's Economy. In this research the Micro Waqf Bank (BWM) is a Sharia Microfinance Institution that is registered and supervised by the Financial Services Authority (OJK) which aims to provide access to capital services for low-income people who do not yet have access to financial institutions and ease the burden on people who are ensnared by moneylenders. Micro Waqf Banks also play a role in empowering the community and the community of women around Islamic boarding schools by encouraging the development of their businesses through providing loan funds to productive community business groups and community groups that wish to open businesses. The approach used in this study is descriptive qualitative with data collection methods of observation, interviews and documentation. The results of this study indicate that the Community Economic Empowerment at As'ad Seberang Micro Waqf Bank Jambi City cannot be said to be good and perfect because there are some customers who use borrowed money not as an additional capital for their business but for other purposes such as paying off debt. costs of daily living, medical expenses and others. This has resulted in the objective of establishing Micro Waqf Banks as an institution that provides access to capital for small communities who do not yet have access to formal financial institutions to empower communities around Islamic boarding schools by encouraging business development through providing loan funds to productive community business groups not being fully achieved. In addition, due to the low understanding of customers regarding productive waqf and the purpose of establishing Micro Waqf Banks. Keywords: Management Management, Empowerment, People's Economy.